Failure prediction of T-peel adhesive joints by different cohesive laws and modelling approaches - Alessandro Pirondi (Fracture and Structural Integrity, 2009)
In this work, Cohesive Zone Modelling (CZM) was used to simulate failure of T-peel bonded joints with 1.5mm thick adherends, respectively, bonded toghether with Loctite Multibond 330 adhesive. The fracture toughness and load-opening behaviour recorded in previous experiments on bonded Double Cantilever Beam (DCB) specimens were taken as reference to calibrate CZM parameters. Two-dimensional models were analysed using the FE code ABAQUS. The failing interface was modeled with the cohesive elements available in this software. The influence of: i) different cohesive law shapes, ii) modeling the presence of the adhesive layer explicitly, was studied.